Coping strategies among brazilian professional and amateur football players - Verardi, Carlos Eduardo Lopes [UNESP]; Neiva, Cassiano Merussi [UNESP]; Pessôa Filho, Dalton Müller [UNESP]; De Oliveira Santos Miyazaki, Maria Cristina; Nagamine, Kazuo Kawano [UNESP]; Da Silva Lobo, Ana Paula; Domingos, Neide Aparecida Micelli; Furukawa, Marcelo (My University, 2012)
To identify coping strategies used among professional and amateur Brazilian football players. The Ways of Coping Scale (WOCS) was completed by 134 male football players (71 professionals: mean age = 22.77 ± 3.98 years; 63 amateurs: mean age = 17.18 ± 0.84 years) from three teams that participated in the Campeonatos Estaduais da Primeira Divisão (the state championships for the first division of football). There was no significant difference between the two groups in the type of coping strategy they used (e.g., problem-focused, emotion-focused, fantasy thoughts, religious practices and social support). Problem-focused coping was the most frequently used strategy by all of the players and social support was the least frequently used strategy. Both professional and amateur players failed to focus on the development of adequate coping strategies. Further studies are needed to better understand the impact that Brazilian athletes experience has on their choice of coping strategies during pre-competitive and competitive phases of their sport. © JPES.
Keywords: Amateur; Football; Professional; Psychological adaptation